Optically- and thermally-induced electronic transitions in a three-level system. (23rd September 2020) - Qiu, Ming-Yang; Jin, Wei; Qu, Shi-Xian; Li, Chun; Lefkidis, Georgios; Hübner, Wolfgang
Abstract: In this article, using the Lindblad-superoperator formalism, we study the laser-induced electronic transitions of a Λ process in a three-level model system coupled to an external thermal bath. We find that, with respect to the population transfer from the initial to the final state, when the two branches of the thermal transitions (i.e., initial to intermediate state and intermediate to final state) are symmetric, the unbalanced optical channels can enhance the fidelity of the dynamics. Especially for the case where one of the two optical branches is totally forbidden, the fidelity still reaches the maximal value due to the compensation by the thermal transition channel, leading to a population trapping in the final state (thermally assisted Λ process). On the other hand, with the increase of the unbalanced thermal channels in the case of symmetric optical transitions, the fidelity of the process does not change but the speed for the dynamics to reach the steady state slows down. Additionally, we investigate and analyze the role of the bath temperature, of the coupling constant to the thermal bath, as well as of a time-dependent energy shifting of the final state. For the last aspect, followed by the detailed symmetry analysis, its application on a realistic Ni2 molecule is presented. The results are expected to be highly relevant to the active manipulation of spins in real nanospintronic devices at room temperature.